Dāḥ. Bi.Si. Rāẏa, janmaśatabārshikī smārakagrantha, 1981-1982 (Ḍāḥ. Bi.Si. Rāẏa Memoriẏāla Kamiṭi, 1981)
On the life and works of Dr. Bidhan Chandra Roy, 1882-1962, former chief minister of West Bengal.